Loss of water from protonated polyglycines: interconversion and dissociation of the product imidazolone ions. Issue 27 (29th June 2018) - Lam, K. H. Brian; Lau, Justin Kai-Chi; Lai, Cheuk-Kuen; Chu, Ivan K.; Martens, Jonathan; Berden, Giel; Oomens, Jos; Hopkinson, Alan C.; Siu, K. W. Michael
Abstract : Imidazolones formed from polyglycines are located at the centre of the peptide backbone and dissociate more easily than interconvert. Abstract : Collision-induced dissociation of isotopically labelled protonated pentaglycine produced two abundant [b5 ] + ions, the products of the loss of water from the first and second amide groups, labelled [b5 ] + I and [b5 ] + II . IRMPD spectroscopy and DFT calculations show that these two [b5 ] + ions feature N1 -protonated 3, 5-dihydro-4 H -imidazol-4-one structures. 15 N-Labelling established that some interconversion occurs between these two ions but dissociations are preferred. For both ions, DFT calculations show that the barrier to interconversion is slightly higher than those to dissociation. Dehydration of protonated hexaglycine produced three imidazolone ions. Ions [b6 ] + I and [b6 ] + II exhibit analogous CID spectra to those from [b5 ] + I and [b5 ] + II ; however, the spectrum of the [b6 ] + III ion was dramatically different, showing losses predominantly of a further water molecule or cleavage of the second amide bond to give the glycyloxazolone (a deprotonated [b2 ] + ion, labelled GlyGlyox (114 Da)) from the N-terminus. Protonated polyglycines [Gly n + H] +, where n = 7–9, all readily lose at least one water molecule. The corresponding [b n ] + ions lose either a further water molecule, an oxazolone from the N-terminus or a truncated peptide from the C-terminus. The number of amino acid residues in the latter two eliminated neutral molecules provides insight into the location of the imidazolone in the peptide chain and which oxygen was lost in the initial dehydration reaction. From this analysis, it appears that water loss from the longer protonated polyglycines is predominantly from the central residues.